Extreme events induced by climate change alter nectar offer to pollinators in cross pollination-dependent crops - Maria Luisa P. Frigero; Carmen S. F. Boaro; Leonardo Galetto; Priscila Tunes; Elza Guimarães (Scientific Reports, 2025)
Abstract Both severe reductions and increases in rainfall can stress plants and modify floral traits involved in plant-pollinator interactions, such as nectar production. Animal pollination is responsible for most plant species’ reproduction including several crops that rely especially on bees for fruit and seed production. Thus, extreme climate events can cause disruptions in pollination mutualism and lead to a decrease in the production of many crops worldwide. This study investigated the effects of changes in rainfall on nectar availability to pollinators at flower-, plant- and agricultural-scale, using an outcrossing bee-pollinated model crop. We experimentally simulated four scenarios: Control, Heavy rainfall, Rainfall reduction and Drought. All treatments but Rainfall reduction affected nectar traits at flower-scale. At plant- and agricultural-scale, Heavy rainfall increased nectar caloric offer (+ 79% and + 74%, respectively), while Rainfall reduction and Drought decreased it (− 37% and − 34%; − 98% and − 95%, respectively). Thus, drought treatments resulted in less resources available to pollinators The predicted rainfall shifts mediated by climate change may negatively affect cross-pollinated crops worldwide, as changes in nectar traits are prone to affect pollinator foraging behaviour and energy intake rate, decreasing pollination and fruit production. In summary, food security for humans may be closely linked to food security for pollinators.